Bioplastics in the Sea: Rapid In-Vitro Evaluation of Degradability and Persistence at Natural Temperatures - Miksch, Lukas; Köck, Matthias; Gutow, Lars; Saborowski, Reinhard (Frontiers in Marine Science, 2022)
The progressive substitution of petroleum-based polymers, such as polyethylene, polyvinylchloride, or polyethylene terephtalate, by so-called bioplastics facilitated the development and production of many new materials. The continuously refined properties of bioplastic compounds and their blends enable various applications. With growing production and utilization of bioplastic products, these materials are increasingly discarded into the environment. Although many of these materials are labeled biodegradable, there is limited information about their degradability under environmental conditions. We tested the enzymatic degradability of five bioplastic compounds with the rapid pH-Stat titration assay at environmentally relevant seawater temperatures between 5 and 30°C and pH 8.2. These plastics, issued from the European Horizon 2020 Project ´Bioplastics Europe´, are based on polylactic acid (PLA), polybutylene succinate (PBS), and poly(hydroxybutyrate-co-hydroxyvalerate) (PHBV). Suspensions of microparticles (< 200 µm) were incubated with each of the three hydrolytic enzymes, protease, lipase, and esterase. A PLA-based compound blended with polybutylene adipate terephthalate (PBAT) showed the highest hydrolysis rate of 30 nmol·min-1 when incubated with lipase at 30°C. All other materials showed low hydrolysis rates of less than 10 nmol·min-1. Below 20°C, hydrolysis almost ceased. Plate clearing assays with the same enzymes at 37°C and pH 5 and pH 8, respectively, largely confirmed the results of the pH-Stat titration assays. Our findings indicate that there is a potential degradation of most of the materials with at least one of these hydrolytic enzymes. Nonetheless, the rate of enzymatic degradation under environmentally relevant conditions is low, which indicates only a marginal degradability of bioplastics in the marine environment.